ASSOCIATION BETWEEN TRIGEMINAL NEURALGIA AND UNNECESSARY TOOTH EXTRACTION - Rehman, Abdur; Abbas, Iram; Alamgir; Ghous, Shah Muhammad; Ahmad, Nofil; Ahmad, Ans (Journal of Ayub Medical College Abbottabad, 2021)
Background: Trigeminal neuralgia is a very painful condition which is presented as severe pain corresponding to spastic shock. This is caused by trigeminal nerve’s vascular compression at root entry zone. The pain is induced due to ipsilateral neurovascular conflict. in spite of the condition being known since centuries, it still continues to frustrate the clinician and its pathogenesis remains as enigma to the medical profession. It is very common for these patients to undergo unnecessary dental extraction without any relief in pain. This study was conducted to assess the association between trigeminal neuralgia and unnecessary tooth extraction. Methods: This was a cross-sectional study conducted between January 2017 and July 2019 in the Department of Dentistry of Ayub Teaching Hospital, Abbottabad. A total of fifty-three cases with Trigeminal neuralgia were included. All the patients were evaluated by history, clinical examination and local anaesthetic injection. Results: Fifty-three Trigeminal neuralgia cases were enrolled in this study; out of which 22 cases (41.5%) were males and 31cases (58.5%) were females. Mean age of all the patients was 53.90 years. Twenty-nine patients (54.7%) had their right side involved, while the left side was involved in 23 patients (43.4%). In only one case (1.9%) there was bilateral involvement. Regarding tooth extraction unnecessary extraction were reported by 25 (47.1%) patients before they were diagnosed to have trigeminal neuralgia. The Maxillary first Premolar was the most common tooth extracted. Conclusion: Trigeminal neuralgia is one of the most severe painful condition of the maxillofacial region which can confuse the patient and the Dentist with toothache. Patient should be evaluated in detail to rule out trigeminal Neuralgia before tooth extraction. Keywords: Trigeminal neuralgia; Toothache; Tooth extraction